O PODER DE ZEFERINA NO QUILOMBO DO URUBU UMA RECONSTRUÇÃO HISTÓRICA POLÍTICO-SOCIAL - Barbosa, Silvia Maria Silva (2003)
The ideals of liberty demanded differentiated practices from blacks in order to break with the system of slavery. They were shipboard rebellions, the killing of infants, judgments of chiefs, revolts, besides participation in libertarian movements and the formation of quilombos. Within these, the quilombo was an essential phenomenon in the more than 300 years of slavery in Brazil. Quilombos could be found in each region, since for the black population, captive or not, this was the best means of attaining freedom, a collective means of confronting the system.The Quilombo of Urubu represented resistance by guaranteeing humane conditions that the slave regime denied black men, children, and above all women. It was a force that came from the very bowels as a cry for liberty, given form through flights in search of a place that provided at least an approximation of a life with dignity, and where they could be proud of their physical bearing, and culture. This quest for freedom demanded, beyond physical force, an apparatus of resistance that had its source in historical and spiritual knowledge, maintained by a religiosity that provided the spiritual strength necessary to fight against the negation of humanity of the XIX century in the periphery of the region of Bahia. The leader, Zeferina, moved by the social exclusion of blacks, and given impetus by the power of ancestral legacy, by the knowledge of the roots of matrilineal Angolan culture, by a profound knowledge of the historical resistance of queen Nzinga Mbandi, and by the tradition of quilombolas and warrior women lived and fought for the dream of freedom. Today, the flame of this power is continued in the celebrative walk of the 20th of November by the community of Pirajá and the surrounding region as a reference to black resistance in the fight against current social exclusions.(AU)